ECCU (E-cadherin/catenin) complex and its role in carcinogenesis - Ozga, Alicja Maria; Obuchowska, Aleksandra; Wójcik, Justyna; Standyło, Arkadiusz; Piotrowska, Paulina (Journal of Education, Health and Sport, 2020)
Introduction: One of the main characteristics of cancer is uncontrolled cell proliferation as well as loss of cells adhesion in the case of metastases. Cadherins and catenins are the molecules responsible for cell-to-cell interaction. Together, they form a complex called ECCU (E-cadherin/catenin complex) which maintains the proper tissue structure. However, an impairment in its functioning can result in many adverse health effects, such as cancer promotion. Purpose: To evaluate the potential role of ECCU complex in carcinogenesis. Materials and methods: We performed the database research using PubMed, Springer Link and ResearchGate and we made review and meta-analysis of relevant studies. We searched for studies analyzing the relationship between ECCU complex and carcinomas development. Results: ECCU takes part in many cell processes and pathways, such as Wnt/Wingless‐signaling pathway or EMT/MET processes. It interacts with various molecules, for instance p27 protein or transcription factors. Aberrations in the expression of ECCU components is related to carcinoma promotion, shorter survival rate of patients and poor differentiation of the tumor. Conclusions: A role of the ECCU complex is complicated, however there is a clear correlation between loss of cell adhesion and carcinoma promotion and progression. The complex can be a possible target of anti-cancer therapy in the future; it is also under investigations as a marker of the disease, however it is questionable.